Differential Effects of Coating Materials on Viability and Migration of Schwann Cells - Klein, Silvan (Materials (Basel), 2016)
Synthetic nerve conduits have emerged as an alternative to guide axonal regeneration in peripheral nerve gap injuries. Migration of Schwann cells (SC) from nerve stumps has been demonstrated as one essential factor for nerve regeneration in nerve defects. In this experiment, SC viability and migration were investigated for various materials to determine the optimal conditions for nerve regeneration. Cell viability and SC migration assays were conducted for collagen I, laminin, fibronectin, lysine and ornithine. The highest values for cell viability were detected for collagen I, whereas fibronectin was most stimulatory for SC migration. At this time, clinically approved conduits are based on single-material structures. In contrast, the results of this experiment suggest that material compounds such as collagen I in conjunction with fibronectin should be considered for optimal nerve healing.